Current trends in forensic odontology - Jeddy, Nadeem (J Forensic Dent Sci, 2017)
Forensic odontology is an evolving science and has a greater scope of development. It has established as an indispensable science in medico-legal matters and in the identification of the dead person. The dental tissues are often preserved even if the deceased person is skeletonized, decomposed, burnt, or dismembered. Various methods have been developed to determine age, sex, and ethnicity of the person, using dental tissues. Data collection methods and supplementary technologies used in forensic dental identification have undergone significant transformation. This article provides an overview of the evolving trends in conventional methods, and the recent concepts used in forensic odontology.